2010
DOI: 10.1007/s11458-010-0220-7
|View full text |Cite
|
Sign up to set email alerts
|

Probing polymer surfaces and interfaces using sum frequency generation vibrational spectroscopy - a powerful nonlinear optical technique

Abstract: Sum frequency generation (SFG) vibrational spectroscopy has been proved to be a powerful technique which substantially impacts on many research areas in surface and interfacial sciences. This paper reviews the recent progress of applying this nonlinear optical technique in the studies of polymer surfaces and interfaces. The theoretical background of SFG is introduced first. Current applications of SFG in polymer science are then described in more detail to demonstrate the significance of this technique. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Sum frequency generation (SFG) vibrational spectra were obtained by a custom-designed EKSPLA SFG spectrometer, which has been described in detail by various researchers. Briefly, the visible input beam at 0.532 μm was generated by frequency doubling a part of the fundamental output from an EKSPLA Nd:YAG laser. The IR beam, tunable between 1000 and 4300 cm –1 (with a line width < 6 cm –1 ) was obtained from an optical parametric generation/amplification/difference frequency generation (OPG/OPA/DFG) system based on LBO and AgGaS 2 crystals, which were pumped by the second harmonic and the fundamental output of the laser.…”
Section: Methodsmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectra were obtained by a custom-designed EKSPLA SFG spectrometer, which has been described in detail by various researchers. Briefly, the visible input beam at 0.532 μm was generated by frequency doubling a part of the fundamental output from an EKSPLA Nd:YAG laser. The IR beam, tunable between 1000 and 4300 cm –1 (with a line width < 6 cm –1 ) was obtained from an optical parametric generation/amplification/difference frequency generation (OPG/OPA/DFG) system based on LBO and AgGaS 2 crystals, which were pumped by the second harmonic and the fundamental output of the laser.…”
Section: Methodsmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy has been developed into a powerful probe to study the surface and interfacial structures at the molecular level. For example, it successfully elucidated molecular structures of various polymer surfaces and interfaces. , This technique intrinsically detects the second-order nonlinear susceptibility at polymer surfaces and interfaces in that the second-order nonlinear susceptibility of the polymer bulk vanishes under the electric dipole approximation. The generally used sample geometry in the SFG study was a polymer thin film on a substrate. , In this case, the polymer thin film was taken as a nonlinear polarization sheet which can generate the SFG signals, as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the above requirements can be achieved by a second-order nonlinear optical technique–sum frequency generation (SFG) vibrational spectroscopy, which has been developed for 30 years. This coherent optical technique has the intrinsic monolayer/submonolayer sensitivity and surface/interface selectivity to probe the detailed molecular-level structural information at surfaces or interfaces, thus offering a powerful analytical way to study different materials, including polymers. Previous work has demonstrated that the surface restructuring of polymeric materials can be investigated upon contact with water, organic solvents, or treatment with surface plasma by using the SFG vibrational spectroscopy. ,,,, However, a systematic molecular-level study using SFG on an antifouling polymer surface in air, surface in contact with water/protein solution, and buried polymer/substrate interface upon water exposure has not been fully conducted yet, and there still remain important scientific issues to be studied.…”
Section: Introductionmentioning
confidence: 99%